Carcinoma of the cervix and tobacco smoking: collaborative reanalysis of individual data on 13,541 women with carcinoma of the cervix and 23,017 women without carcinoma of the cervix from 23 epidemiological studies. - Appleby, P; Beral, V; Berrington de González, A; Colin, D; Franceschi, S; Goodill, A; Green, J; Peto, J; Plummer, M; Sweetland, S (2006)
Tobacco smoking has been classified as a cause of cervical cancer, but the effect of different patterns of smoking on risk is unclear. The International Collaboration of Epidemiological Studies of Cervical Cancer has brought together and combined individual data on 13,541 women with and 23,017 women without cervical carcinoma, from 23 epidemiological studies. Relative risks (RRs) and 95% confidence intervals (CIs) of carcinoma of the cervix in relation to tobacco smoking were calculated with stratification by study, age, sexual partners, age at first intercourse, oral contraceptive use and parity. Current smokers had a significantly increased risk of squamous cell carcinoma of the cervix compared to never smokers (RR = 1.60 (95% CI: 1.48-1.73), p<0.001). There was increased risk for past smokers also, though to a lesser extent (RR = 1.12 (1.01-1.25)), and there was no clear trend with time since stopping smoking (p-trend = 0.6). There was no association between smoking and adenocarcinoma of the cervix (RR = 0.89 (0.74-1.06) and 0.89 (0.72-1.10) for current and past smokers respectively), and the differences between the RRs for smoking and squamous cell and adenocarcinoma were statistically significant (current smoking p<0.001 and past smoking p = 0.01). In current smokers, the RR of squamous cell carcinoma increased with increasing number of cigarettes smoked per day and also with younger age at starting smoking (p<0.001 for each trend), but not with duration of smoking (p-trend = 0.3). Eight of the studies had tested women for cervical HPV-DNA, and in analyses restricted to women who tested positive, there was a significantly increased risk in current compared to never smokers for squamous cell carcinoma (RR = 1.95 (1.43-2.65)), but not for adenocarcinoma (RR = 1.06 (0.14-7.96)). In summary, smokers are at an increased risk of squamous cell but not of adenocarcinoma of the cervix. The risk of squamous cell carcinoma increases in current smokers with the number of cigarettes smoked per day and with younger age at starting smoking.